Using defined daily doses to review antibiotic prescribing. Issue 8 (15th September 2021) - Motta, Marco; Wilcock, Mike; Heald, Adrian
Abstract : Optimising antibiotic prescribing in the primary care setting is a key component of the UK antimicrobial resistance (AMR) strategy. In this project, the authors worked with eight GP practices in Cornwall that had high levels of antibiotic prescribing to help them find ways to improve their prescribing and reduce antibiotic consumption, using defined daily doses (DDDs) as a measure of consumption.